(untitled) (The Review of Diabetic Studies, 2024)
Background: In the Critical Care Unit (ICU), patients have a high death rate because of their complexity. One important factor that can enhance patient care is palliative care (PC).. Therefore, the aim of this study was to assess Critical Care nurses’ knowledge regarding Palliative Care. An exploratory descriptive research design was adopted. Setting and sample: During the study period, a convenience sample of all the critical care nurses working in the Saudi hospital’s critical care units (a total of 74 nurses) was included. Two tools were used: Tool (1): Background information about nurses, Tool (2): questionnaire about critical care nurses’ knowledge regarding palliative care. Results: The mean age of the nurses in the study was 29.167.27 years, and more than half of them were female and had less than five years of experience. The majority of nurses had adequate understanding of psychological and spiritual care, pain and symptom management, and the philosophy and principles of palliative care, while only had insufficient knowledge of these topics. Conclusion: Based on the results it concluded that Nurses’ overall mean knowledge scores regarding palliative care were poor Recommendations: Develop in service training programs to raise the nurses’ standards about palliative care.